The development and pilot randomised controlled trial of a group education programme for promoting walking in people with intermittent claudication. (August 2015) - Tew, Garry A; Humphreys, Liam; Crank, Helen; Hewitt, Catherine; Nawaz, Shah; Al-Jundi, Wissam; Trender, Hazel; Michaels, Jonathan; Gorely, Trish
The aim of this study was to develop and pilot a group education programme for promoting walking in people with intermittent claudication. Patient focus groups ( n =24) and literature reviews were conducted to inform the development of the education programme, which involves a three-hour group-based education workshop and follow-up telephone support. A pilot study was subsequently conducted in which 23 new patients (Rutherford category 1–3) were randomly assigned to usual care (control) or usual care plus the education programme. Outcomes were assessed at baseline and six weeks including daily steps (tri-axial accelerometer), walking capacity (six-minute walk test and Gardner treadmill test), and quality of life (Intermittent Claudication Questionnaire [ICQ]). Exit interviews were conducted to assess the acceptability and usefulness of the programme. Compared with controls, the intervention group had superior walking capacity and quality of life at six weeks. Mean differences in six-minute walk distance, treadmill maximum walking distance and ICQ score were 44.9 m (95% confidence interval [CI], 6.9 to 82.9), 173 m (95% CI, 23 to 322), and −10.6 (95% CI, −18.9 to −2.3), respectively. The daily step count did not differ between groups. The exit interviews indicated that participants valued attending the programme, that it gave them a greater understanding of their condition, and that they had been walking more for exercise since attending. The results suggest that the education programme is feasible, acceptable, and potentially useful for improving walking capacity and quality of life. A fully-powered trial exploring clinical and cost effectiveness is needed. TRIAL REGISTRATION NUMBER: ISRCTN06733130 (http://www.controlled-trials.com ).